An analysis of the Return on Assets of HoReCa Companies in Constanta County in the Context of the Recovery Pursuits after the Shock Produced by the COVID-19 Pandemic - Aivaz, Kamer-Ainur; Căpățână, Alexandru (Technium Social Sciences Journal, 2021)
From a microeconomic perspective, if we refer to a company as an economic agent, its organizational resilience/flexibility, in the unprecedented global economic context generated by COVID-19, is in the limelight, given that a resilient company would design and implement effective actions in order to increase the probability of its own survival. Assuming that a company’s assets are those means by which a company can secure an income for a period of several years, since they are economic resources that can generate economic benefits in the future for the company that owns them, we have considered it appropriate to analyse the return on assets at the level of the companies in the HORECA sector. The comprehensive research undertaken is an empirical study in which we have analysed all the companies in the HORECA sector on the territory of Constanta County, located in the coastal area of the Black Sea, for a period of 3 years, 2018-2020, a period which includes the year of the onset of the SARS-COVID-19 pandemic. The selected economic and financial indicators have been fixed assets, current assets, prepaid expenses and net profit, with the help of which we have calculated and analysed the return on total assets. Of the many subgroups of the HORECA sector, the "Other Food Services" subgroup, which had the highest return on assets (ROA), proved to be the most flexible and creative subgroup. Catering specialists, exploiting the context generated by the closing of hotels and restaurants, have modified their business so as to amplify the intrinsic value of their products and to become a psychological and social connection for their consumers.